2021
DOI: 10.1007/s10238-021-00735-7
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic MR imaging and endocrine complications in patients with beta-thalassemia: a single-center experience

Abstract: Iron deposition in various organs can cause endocrine complications in patients with transfusiondependent beta-thalassemia. The aim was to investigate the relationship between endocrine complications and pancreatic iron overload using magnetic resonance imaging (MRI). Forty patients with transfusion-dependent thalassemia (TDT) were enrolled in the study. The magnetic resonance imagings of the patients were performed using a 1.5 Tesla Philips MRI scanner. Two out of three patients had at least one clinical endo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Additionally, our study, in parallel with previous reports [ 28 31 ], indicated that liver T2*-value was significantly correlated with pancreatic T2*-value, serum ferritin and serum iron and pancreatic T2*-value showed significant negative correlation with serum ferritin, whereas others have shown no correlation between hepatic and pancreatic iron [ 32 , 33 ]. These controversial results may be attributed to differences in the type of disease, number of subjects, and management.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, our study, in parallel with previous reports [ 28 31 ], indicated that liver T2*-value was significantly correlated with pancreatic T2*-value, serum ferritin and serum iron and pancreatic T2*-value showed significant negative correlation with serum ferritin, whereas others have shown no correlation between hepatic and pancreatic iron [ 32 , 33 ]. These controversial results may be attributed to differences in the type of disease, number of subjects, and management.…”
Section: Discussionsupporting
confidence: 91%
“…As mentioned, musculoskeletal evaluation is important in children and adults, yet there are some other particular aspects [ 110 ]. Pituitary hemosiderosis in children with BTH might predict delayed puberty, short stature and central hypothyroidism [ 22 , 111 , 112 , 113 ]. Interestingly, brain MRI data showed conflicting results regarding IO; noting that the pituitary gland is particularly sensitive to iron deposits following the trend of the other endocrine glands [ 112 ].…”
Section: Thalassemic Endocrine Diseasementioning
confidence: 99%
“…An MRI-based study on 40 patients with transfusion-dependent TH identified that iron deposits are positive in 62.5% of persons in the liver, 45% in the pancreas, and 12.5% in the heart. Three out of fifty patients had at least one ED [ 113 ]. The cardiac T2* sequence evaluating iron upload negatively correlates with fasting glycaemia ( p = 0.03); subjects with short stature had increased cardiac iron overload ( p = 0.01).…”
Section: Thalassemic Endocrine Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Later, additional methods for monitoring ICT were developed, namely magnetic resonance imaging (MRI) for assessment of liver iron concentration (LIC) and T2* for cardiac iron load for monitoring chelator efficacy or stratifying end-organ risk. 4 Each method has pros and cons to quantifying and monitoring iron burden. When intensification of chelation is required for patients with a very high iron burden, combination therapy is used.…”
Section: Introductionmentioning
confidence: 99%